Properties of juvenile wood of Schizolobium parahyba var. amazonicum (paricá) under different cropping systems - da Silva, Camila Balby Ribeiro; dos Santos Junior, Jose Alves; Araújo, Anselmo Júnior Corrêa; Sales, Agust; Siviero, Marco Antonio; Andrade, Fernando Wallase Carvalho [UNESP]; Castro, Jonnys Paz; de Figueiredo Latorraca, João Vicente; de Lima Melo, Luiz Eduardo (Springer Nature, 2019)
Schizolobium parahyba var. amazonicum (paricá) has been demonstrating good silvicultural performance when cultivated in Agroforestry systems in the Amazon. However, the effects of this cultivation system on wood properties is unknown. The objectives of this research are to understand the effects of the cultivation system on the anatomical characteristics, and physical and mechanical properties of paricá wood. The material used in this study was obtained from an experiment in the southwest region of the state of Pará, Brazil. The treatments included an agroforestry system (AFS) of paricá in consortium with soy (Glycine max), in the first year, corn (Zea mays) in the second and a monoculture only with the studied species. Our results demonstrated significant differences in soil chemical attributes among treatments: the soil in the AFS showed higher levels of phosphorus (P), calcium (C) and copper (Cu) than the soil of the monoculture system. The wood produced in the AFS is significantly different in relation to the monoculture system: wood density and the resistance to compression parallel to fibers being lower in AFS. Furthermore, the AFS presented significant statistical effects on some anatomical characteristics of the wood. Higher values for tangential diameter of vessel lumina and for ray frequency were found. The alterations in wood properties were mainly related to the high concentration of phosphorus in the AFS soil, which can affect the tree growth rates and cambial activity.
Keywords: Agroforestry system; Anatomical features; Density; Mechanical properties; Paricá wood